'Who are the 'Other' visiting my village?' Profiling the domestic tourist market to ethnic villages in Vietnam's Cetral Highlands - Nguyễn, Thị Thanh Kiều (Calla) (2023, 2023)
Understanding tourist markets is important to design appropriate tourism products to satisfy certain types of tourists (Boley & Nickerson, 2013). By conducting a survey of 438 domestic tourists visiting the Central Highlands of Vietnam, the study found that respondents travelling to ethnic villages were highly motivated by Relationship, Novelty, Relaxation/Escape, and Nature factors rather than Host-site involvement or cultural exoticism. Approximately one-third of respondents were ‘true’ ethnic tourists, who were involved in intense ethnic tourism activities in both local private house (30.4%) and other settings (23.4% - 39%). Most respondents participated in superficial and commercial tourism activities in ethnic touristic attractions/facilities (74.9% - 93.5%). Despite being generally satisfied with their trip to the region, respondents were neutral about learning more ethnic culture or building long-term relationship with the locals.